Humanização em saúde: a vivência em uma instituição de ensino - Rafaela Reis da Silva (2018)
In 2003, the Ministry of Health launched the Política Nacional de Humanização, with aim to offer quality care in all areas of health by adding technology to good interpersonal relationships, which is a guiding axis of care and management practices in all instances of SUS. Humanization in health is a network of permanent and solidary construction of ties of citizenship, where the professional passes to look at each individual integrally, taking into account its history, treating it as inserted in a collective. Then the aim of this study was to understand the perception of humanization in dental care among teachers, employees and students of the Faculty of Dentistry of the Federal University of Minas Gerais. The reason for this study is that the results should not be restricted to the scientific community, but would bring a return to society by breaking down barriers to humanization practices in the institution. When working with perception, we choose the qualitative methodology, with a focus group approach. The study participants were teachers, with activities in integrated clinics or specialties, from different areas; employees working in administrative areas of public service or with activities in clinics; and students from various periods involved in clinical college attendance. Each group consisted of six participants grouped by segment, intentionally selected, who were willing to collaborate with the study. This type of sample have been chosen for providing a diversity of opinions. The guidelines for the focus group were drawn from the Guidelines for the National Humanization Policy, addressing three of the dimensions described in it: reception, extended clinic and the defense of users rights. The results were interpreted based on Symbolic Interactionism, with the following themes being identified: Perception of Humanization, Humanization and Teaching; Users rights and Humanization in practice. With this research, it was possible to observe that there are still difficulties in working humanization in education, even after the curricular changes advocated by current policies, which reiterates the need to work on this topic throughout the graduation course in this institution.